IB-DFE receiver techniques for CP-assisted block transmission within DS-CDMA and MC-CDMA systems - Dinis, Rui (2009)
MC-CDMA (MultiCarrier Code Division Multiple Access), currently regarded as a promissing multiple access scheme for broadband communications, is known to combine the advantages of an OFDM-based (Orthogonal Frequency Division Multiplexing), CP-assisted (Cyclic Prefix) block transmission with those of CDMA systems. Recently, it was recognised that DS-CDMA (Direct Sequence) implementations can also take advantage of the beneficts of the CP-assisted block transmission approach, therefore enabling an efficient use of FFT-based (Fast Fourier Transform), chip level FDE (Frequency- Domain Equalisation) techniques. In this paper we consider the use of IB-DFE (Iterative Block Decision Feedback Equalisation) FDE techniques within both CP-assisted MC-CDMA systems with frequency-domain spreading and DS-CDMA systems. Our simulation results show that an IB-DFE receiver with moderate complexity is suitable in both cases, with excellent performances that can be close to the single-code matched filter bound (especially for the CP-assisted DSCDMA alternative), even with full code usage.